Implementasi Program Adiwiyata dalam Kegiatan UKS dan Pengelolaan Sampah dengan Pendidikan Moral di Madrasah Ibtidaiyah Paseban Jember - Khotimah, Khusnul; Sholihah, Mar’atus (Ibtida'iy : Jurnal Prodi PGMI, 2026)
Environmental problems such as pollution, waste accumulation, and low hygiene behavior indicate the importance of integrating environmental education with moral education since the Madrasah Ibtidaiyah level. The purpose of this study is to analyze the implementation of the Adiwiyata Program in building the values of responsibility, discipline, and religiousness through environmental health activities, cleanliness, and waste management as a means of character building for students. This study uses a qualitative approach with a phenomenological type. The research subjects include the Madrasah Principal, the Adiwiyata team, teachers, and students. Data collection in this study was carried out through in-depth interviews, observation, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions. Data validity was strengthened through source purposive sampling. The results of the study show that hygiene habits are carried out through class and prayer room duty, routine community service, garden maintenance, maintaining the cleanliness of 2 toilets, namely teachers and students, and the habit of saving water and electricity. Waste management based on 3R (Reduce, Reuse, Recycle) through sorting organic and inorganic waste, making compost, and utilizing used goods as learning media. The values of responsibility, discipline, and religion are internalized through duty duty, compliance with regulations, manners to teachers, greeting guests, and the use of ablution water to water plants gradually from grades 1 to 6. The Adiwiyata program has proven to function as a means of contextual and sustainable moral education.